Implementation of Position Auction Promotion through the "Assessment Center" in Aceh Province - Deni Setiawan; Suswanta Suswanta; Muhammad Rafi (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2021)
The promotion of the position auction through the "assessment center" is an effort to reform the bureaucracy by the Aceh provincial government. This is done as a response from the government to the image of services that were previously deemed not optimal and to improve the quality of effective and efficient public services. This study aims to determine the process of implementing a promotion auction for positions through an assessment center in Aceh Province. qualitative research methods. This study found that the Aceh provincial government had carried out a position auction promotion to fill the vacancy of structural positions held. This is done as a step in improving government performance to make it more optimal. The auction of this position carried out by the Aceh Provincial Government will be seen by involving the Aceh Civil Service Agency (BKA) against Law no. 5 of 2014 which regulates the state civil apparatus. It is hoped that the results of the promotion of the position auction will eventually be able to place relevant structural officials with better capabilities and performance.